Shock & vibration, aircraft/aerospace, energy harvesting, acoustics & optics. proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 /: proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016. Volume 9 : (2016) - Unknown
No abstract available